Problem Solving In Teaching Grammar - Syafiyah, Syafiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2001)
This article provides an alternative to grammar teaching, namely problem solving techniques. This technique was chosen by considering the many similarities possessed by the process of mastering a language. Besides that, this technique is also considered to be more attractive to students' learning interests. In the first part of this paper, we will describe how the role of grammar in various approaches. Next, the concepts of grammar-consciousness raising will be discussed and how this problem solving technique is applied in the classroom.